The Effectiveness of Codman Pendulum Exercise and Scapular Mobilization to Reduce Pain in Frozen Shoulder Conditions - Iit Selviani; Ardo Okilanda; Riand Resmana; Arisman Arisman (Universitas PGRI Palembang, 2023)
Frozen shoulder is an idiopathic condition of the shoulder characterized by the onset of pain and limitation in the shoulder joint. Frozen shoullder is more common in women than men and occurs in the age range of 40 to 65 years. Problems that arise due to frozen shoulder can be given intervention or Codman Pendular exercise and scapular mobilization techniques. The purpose of this study is aimed at frozen shoulder sufferers to reduce pain. The exercises given in this frozen shoulder condition are Codman Pendular exercise and Scapular Mobilization. This research method is a mental experimental study with pre and post test group design by comparing the level of previous and subsequent pain measured with visual measuring instruments analoge scala (VAS), against the provision of codman pendular exercise and scapular mobilization in frozen shoulder conditions for 4 weeks. Results: Analysis of pain loss difference test with visual analoge scale (vas) in the sample group with a significant value of p = 0.0001 which shows a < of 0.05 which means there is an effect on the effectiveness of exercise administration Codman Pendular Exercise and Scapular Mobilization in reducing frozen shoulder pain.